Utility Tokens, Network Effects, and Pricing Power - Shakhnov, Kirill; Zaccaria, Luana (Management Science, 2023)
We examine digital product markets in which consumers are heterogeneous in their propensity to actively interact with other users and valuations increase with the share of active users (e.g., social network platforms). We propose a model in which entrepreneurs can issue digital claims (tokens) to promise exclusive access to benefits that specifically enhance the utility of active users. This allows entrepreneurs to extract consumer surplus through price discrimination. Because there is an incentive to renege on the “exclusivity” promise ex post and expand the network of active users, the credibility of this commitment resides in a costly technology (blockchain) that embeds automatic contracts in the tokens sold and limits entrepreneurial discretion. We show that the profitability of token-based sales increases with entrepreneurial ability and the intensity of network effects. This paper was accepted by Will Cong, Special Section of Management Science: Blockchains and Crypto Economics. Supplemental Material: The internet appendix and data are available at https://doi.org/10.1287/mnsc.2023.4917 .